Assessing the Adaptive Capacity of Households to Climate Change in the Central Rift Valley of Ethiopia - Mesfin, Demamu; Simane, Belay; Belay, Abrham; Recha, John W.M.; Schmiedel, Ute (MDPI, 2020)
This paper explores the different components of the adaptive capacity of households in the Central Rift Valley (CRV) of Ethiopia and quantifies their relative contributions. The data were derived from a survey of 413 households randomly selected from four Kebeles (the smallest government administrative units) in the CRV. The adaptive capacity of the households was assessed using the Local Adaptive Capacity (LAC) framework and measured in terms of both aggregate and composite indices, with sixty indicators distributed across five major components and subcomponents. The index score for major components shows that intangible variables such as institutions and entitlements, knowledge and information, and innovation contributed to adaptive capacity better than decision–making and governance and asset–base. The composite indices for sub–components showed that the contribution of woodlands to adaptive capacity was positive and superior to other natural assets. Grazing land was the next best contributor, while farmland and water resources made a much lower contribution. The findings of this study are useful to better understand the nature of adaptive capacity and its components at the household level. This study suggests the need for an integrated assessment and enhancement of adaptive capacity with all its components rather than focusing only on asset possession as an indicator of adaptive capacity.